A Mountain to Climb: The Labour Together 2019 Election Review. Issue 3 (21st July 2020) - Surridge, Paula
Abstract: The Labour Together review of the 2019 election brings together polling data, survey data, interviews, and submissions from across the Labour movement. An unpopular leader, tensions around the Brexit position, and a manifesto which was not seen as credible, are all found to have contributed to the scale of the defeat, but Labour's unexpectedly strong performance in 2017 also masked long‐term issues in its connection with the electorate and within the party's campaign organisation. The report attempts to move beyond simply diagnosing the difficulties the party faces, but some of the thorniest issues for the party to resolve are nonetheless left unresolved.